Utilization of Used Cardboard and Vegetable Waste as Growth Media for White Oyster Mushroom (Pleurotus ostreatus) - Lavenia, Jovita; Prasetyaningsih, Aniek; Ariestanti, Catarina Aprilia (Universitas Atma Jaya Yogyakarta, 2021)
White oyster mushroom (Pleurotus ostreatus) is a highly nutritious food with simple cultivation process using sawdust as its main substrate. Nowadays, availability of sawdust become a problem for some mushroom farmers. Cardboard and vegetable wastes are easily found and difficult to maintain. Based on their characteristics, those wastes can be used as mushroom growth media. This study aims to determine the effect of cardboard and vegetable waste on mushroom growth and the best media composition to obtain maximum productivity. Those wastes are used as the main substrate in eleven composition variations with complete randomized design (CRD) analysis method using One-Way ANOVA and simple linear regression statistical test. The results showed, variations in media composition affect the condition of the media which then influence the growth of P. ostreatus. Maximum productivity was found in media composition XI with mycelium growth rate up to 3.91 cm/day, media IX with the biological efficiency up to 45.38%, and media X with the highest total yield up to 97.28 grams. From this study it can be concluded that cardboard and vegetable waste can be an alternative growth substrate for P. ostreatus in urban areas with a maximum concentration of vegetable waste no more than 30% by weight of the media used.